Drone based delivery system: Restrictions and limitations - Azamat Seidakhmetov; Omid Fatahi Valilai (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Considering the idea of drone application in last mile delivery, this paper has examined literature studies about the restrictions and pitfalls which the organizations will face with for using drones in the last mile delivery. Moreover, the recent drone tests for commercial purposes in last mile delivery industry and challenges in these practices are investigated. Methodology: A survey-based approach has been applied to both the potential customers of the drone delivery service and also literature review for discovery of latest practices for drone enabled delivery projects has been targeted to identify the limitations and restrictions. Findings: The study demonstrates the problems that arise when the delivery drone crushes while in the air and the approach of self-exploding drones does not seem to make positive effect on this problem. Also, issues like special area for landing, noise of drone activities, safety and security of citizens in urban area are found to be main concerns. Originality: Very few research studies have been conducted in evaluation of using drones for last mile delivery operations focusing on current limitations and forthrightly downsides of drones of current state of the art. Therefore, this paper has tried to elaborate the limitations and restrictions from two perspectives of potential customers and technology developers.
urn:nbn:de:gbv:830-882.0200907; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Technology Management; Innovation Management